Link Quality Prediction Based On Gradient Boosting - Shu Jian, Liu Linlan (International Journal of Advanced Science and Technology, 2020)
To predict the consistency of the connections in the Wireless Sensor Network (WSN), which can aid inthe selection of links for the upper layer protocol. In this article we proposed a GBM (GradientBoosting Machine)-based prediction of the relation efficiency. This measures the relation parameters(RSSI, LQI, SNR, and PRR) and trains the model to predict the future value of PRR based on realexperimental data. Experimental findings suggest that our proposed LQP-GBM prediction accuracyindicates the efficacy of LQP-GBM as compared to CART AND LDA.